SOCIAL SERVICES AS A PLAYGROUND FOR SUPPORT OF THE EDUCATIONAL PROCESS AND TEACHING COMPUTER SCIENCE - Yurchenko , Artem; Mulesa, Pavlo; Loboda, Vasily; Ostroha, Mariia (Physical and Mathematical Education, 2022)
Formulation of the problem. The active development of the information society, information technologies and tools has led to the emergence of virtual social networks, which have become an environment for mass communication of adolescents. The popularization of social services gives rise to the idea of using such a platform for educational purposes. However, despite the large number of studies indicating the great potential for the use of social services in education, there is no consensus on such use. On the one hand, social networks are entertaining, and the teacher’s task is to take students out of this space and direct them to other media and offer other activities. On the other hand, visiting social networks should be made as constructive as possible to increase motivation to learn, and increase students’ interest in learning. Materials and methods. The study used theoretical methods of scientific knowledge (content analysis of Internet resources; theoretical analysis and generalization of foreign scientific research in the field of education and in the use of social networks for education in Ukraine). Results. The article provides a brief overview of social services as platforms for accompanying computer science training. It is shown that the use of the educational network "Diary.ua" is a successful replacement for printed school documents. The "e-schools" resource is an integrated system of electronic diaries and journals, so its use is relevant for educational institutions. The "On Lesson" educational project is a tool to support the study of various subjects at school. For educational purposes, a content analysis of YouTube video hosting materials for the availability of videos on teaching computer science. The most popular resources for the keywords "programming", and "computer graphics" were identified, as well as a brief description of Facebook groups focused on teaching computer science in Ukrainian school curricula. Conclusions. The analysis of social services allows us to state that today they are an integral attribute of schooling. Social networks are often a source of educational resources, including in teaching computer science, so it is worth using their potential for the intellectual development of students and involving young people in various educational activities (research projects, conferences, or competitions of various levels, educational and socio-cultural events). Promising scientific research is the development of methods for teaching certain topics in the school course of computer science using various social networks.